Removal of sulphate and arsenic from wastewater using calcium sulfoaluminate (ye’elimite) - Nurmesniemi, Emma-Tuulia; Huhta, Milla; Derkani, Maryam; Isteri, Visa; Hanein, Theodore; Hu, Tao; Tanskanen, Pekka; Lassi, Ulla (Frontiers in Materials, 2022)
Chemical precipitation is one of the most widely known methods for treatment of industrial wastewaters with high sulphate content, where sulphate can be precipitated as practically insoluble ettringite (Ca6Al2(SO4)3(OH)12·26H2O). This treatment method is also widely recognised for solidifying hazardous components and toxic elements e.g. arsenic in wastewater. In the ettringite precipitation process, lime and aluminium salts are typically used as starting materials, in stoichiometric amounts to form ettringite from the sulphate-containing water, leading to a pH rise to ∼11.5 and ettringite precipitation. In the current study, for the first time, ye’elimite mineral (Ca4Al6O12SO4), also known as calcium sulfoaluminate (CSA) in cements, is used in order to investigate its suitability to form ettringite precipitate from sulphate and arsenic containing synthetic wastewater and industrial wastewater solutions. The dissolution of ye’elimite prior to dosing, optimal precipitation pH, and arsenic co-precipitation were studied. The effluent and precipitates were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM-EDS) and inductively coupled plasma atomic emission spectroscopy (ICP-OES). The results showed that high percentage of sulphate removal (98% in the synthetic wastewater and 87% in the industrial wastewater) can be achieved using ye’elimite as the aluminium source in ettringite precipitation. Additionally, up to 95% arsenic removal was achieved in arsenic co-precipitation experiments from the synthetic wastewater. The current developed technology can be used as a novel ecological and cost-effective approach for removal of sulphate and toxic elements from wastewater.